Avaliação do Plano Estadual de Recursos Hídricos de acordo com a percepção dos membros do CEHIDRO-MT - Azevedo, Stela Amanda Santos de (2021)
Water is essential for life on planet Earth, its growing use, uneven distribution are some factors that led to conflicts, which occurred at regional, state and federal levels. Thus, in order to minimize disparities in water distribution, management is an important tool. Established by law 9433/97, this must be integrated, participatory and decentralized, this occurs so that there is more effective protection of water, in addition there are also state laws, as in the case of the state of Mato Grosso, Law nº 11088/20 which has functions, principles, guidelines and instruments. This inserted in the instruments of the State Water Resources Policy, the object of this study is the State Water Resources Plan, which aims to establish programs and projects for a 20-year horizon and thus guarantee the quantity and quality of water in the State. Therefore, the objective of the work is to present the perception of the members of the State Water Resources Committee of Mato Grosso, in relation to the importance of the programs proposed by the State Water Resources Plan and thus identify which programs are priority, that is, when they are executed reinforce/help or hinder the execution of others. For this, an exploratory and descriptive analysis was carried out, with the application of questionnaires, which were divided into two parts, the first of which was asked to each research interviewee to assign a value from 1 to 19 for each of the 19 programs from PERH, from least important (1) to most important (19). The second part evaluated the interactions between the programs from the perspective of each respondent, for the ten programs that the respondent judged most important. Each completed form generated an actor-actor relationship matrix (programs-programs), in which density and centrality metrics were analyzed. Thus, the program that was cited as a priority was “Record of use and users of Water Resources” and the least priority program was “Soil and water conservation and restoration of riparian forests in micro-basins”. Among the programs that reinforce the others the most is Program III (Development of river basin plans) and the one that most enables the others is Programs II, VI, VII. On the other hand, programs VIII and XI, even if they are not listed as a priority, must be executed together with the others, otherwise the enabling effect of the others can be reduced. Despite the advances so that all PERH programs are effectively implemented, it is necessary to have an order in their execution, because even after several years of execution, the water resources management instruments are still under development and implementation.